2014
DOI: 10.1007/s40204-014-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue engineering scaffolding: computer-aided scaffolding techniques

Abstract: Tissue engineering is essentially a technique for imitating nature. Natural tissues consist of three components: cells, signalling systems (e.g. growth factors) and extracellular matrix (ECM). The ECM forms a scaffold for its cells. Hence, the engineered tissue construct is an artificial scaffold populated with living cells and signalling molecules. A huge effort has been invested in bone tissue engineering, in which a highly porous scaffold plays a critical role in guiding bone and vascular tissue growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
183
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(185 citation statements)
references
References 274 publications
(302 reference statements)
1
183
0
1
Order By: Relevance
“…Porosity, swelling capacity, water absorption, compressive strength and compressive modulus analysis indicated that the physical properties of the scaff old met the basic requirements for use in tissue engineering [30][31][32][33] (Tables 1 and 2). One hour after the start of the experiment, the pH was approximately 7.0.…”
Section: Porosity Swelling Capacity Water Absorption Capacity Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Porosity, swelling capacity, water absorption, compressive strength and compressive modulus analysis indicated that the physical properties of the scaff old met the basic requirements for use in tissue engineering [30][31][32][33] (Tables 1 and 2). One hour after the start of the experiment, the pH was approximately 7.0.…”
Section: Porosity Swelling Capacity Water Absorption Capacity Mechmentioning
confidence: 99%
“…In general, an engineered tissue consists of a scaffold, cells, and essential growth factors [6][7][8] . Scaffolds with high porosity promote bone regeneration and vascularization 9) . therefore, the selection of materials and construction of scaff olds are very important considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various bioceramic-polymer composites for bone-grafting material were prepared and relationship between material structure and properties has been studied. [18][19][20] Among synthetic polymers used in bone tissue engineering the polylactic acid (PLA) is probably the most widely investigated biodegradable and bioresorbable polyester. 21 The degradation of bioceramic-polymer composite in a biological environment is a complex process and often is surface determined.…”
mentioning
confidence: 99%
“…Over the years different technologies have been used for topographical structuring to alter the roughness, surface energy/charge/area, and enhance the cells adhesion, morphology, differentiation, proliferation and osteoconductivity. 18,[22][23][24][25][26][27] Surface of biomaterials can be altered both chemically and physically. In recent decades among physical methods direct laser writing (DLW) gained a lot of attention due to its capability to be used as a versatile tool producing topographical micro-and nanostructures 25,31,32 .…”
mentioning
confidence: 99%
“…However, tissue engineered scaffolds do not completely mimic the native architecture of the tissues, have difficulties to support the growth of cells in 3D and have problems to deposit different cell types in the scaffolds at specified locations [8,9,11,12] . Besides, many of these fabrication methods involve the use of organic solvents which impair the cellular growth [13] . Further, tissue engineered scaffolds do not completely fulfill all the ideal requirements needed for tissue regeneration as discussed above.…”
Section: Introductionmentioning
confidence: 99%